Analisis Metode Outdoor Learning Mengatasi Kejenuhan Belajar IPAS Siswa Kelas V SD Negeri 1 Katapang - Nurhafida Nurhafida; Nathalia Y. Johannes; Samuel Patra Ritiauw (Educatio, 2026)
In order to assess how outdoor learning techniques can help students in grade V of SD Negeri 1 Katapang overcome their boredom with science, this study used a descriptive qualitative methodology. Observation, interviews, and documentation were used to gather data. The study's findings show that using the advantages of nature, outdoor learning is implemented during the planning, execution, and assessment phases. Obstacles found include weather factors, time management, and student control in the field. Solutions taken include schedule adjustments, strengthening group management, and providing supporting facilities. The findings indicate that outdoor learning is an effective strategy to create more meaningful and enjoyable science learning. Keywords: outdoor learning, learning boredom, IPAS, elementary school students.